Influence of carbohydrate on the immune response to intensive, prolonged exercise - Nieman, D. C. (Exercise Immunology Review, 1998)
Many components of the immune system exhibit change after prolonged, heavy exertion, indicating that the immune system is suppressed and stressed, albeit transiently, following prolonged endurance exercise. Whether these immune changes compromise host protection against viruses is still undetermined. Various attempts have been made to alter the changes in immunity following heavy exertion through nutritional or chemical means, with the most impressive results reported thus far in the carbohydrate supplementation studies. Earlier research had established that a reduction in blood glucose levels is linked to hypothalamic-pituitary-adrenal activation, an increased release of adrenocorticotrophic hormone and cortisol, increased plasma growth hormone, decreased insulin, and a variable effect on blood epinephrine levels. Data from two studies of 30 marathon runners and 10 triathletes suggest that carbohydrate compared to placebo ingestion is associated with higher plasma glucose levels, an attenuated cortisol and growth hormone response, fewer perturbations in blood immune cell counts, lower granulocyte and monocyte phagocytosis and oxidative burst activity, and a diminished pro- and anti-inflammatory cytokine response. Overall, the hormonal and immune responses to carbohydrate compared to placebo ingestion suggest that physiologic stress is diminished, although clinical significance awaits further research.